Alkali Activated Materials State-of-the-Art Report, RILEM TC 224-AAM - Provis, John L; van Deventer, Jannie S. J (RILEM State-of-the-Art Reports, 2014)
This is a State of the Art Report resulting from the work of RILEM Technical Committee 224-AAM in the period 2007-2013. The Report summarises research to date in the area of alkali-activated binders and concretes, with a particular focus on the following areas: binder design and characterisation, durability testing, commercialisation, standardisation, and providing a historical context for this rapidly-growing research field.